2021
DOI: 10.1021/acsnano.1c06672
|View full text |Cite
|
Sign up to set email alerts
|

Universal Polymeric-to-Colloidal Transition in Melts of Hairy Nanoparticles

Abstract: Two different classes of hairy self-suspended nanoparticles in the melt state, polymer-grafted nanoparticles (GNPs) and star polymers, are shown to display universal dynamic behavior across a broad range of parameter space. Linear viscoelastic measurements on well-characterized silica-poly­(methyl acrylate) GNPs with a fixed core radius (R core) and grafting density (or number of arms f) but varying arm degree of polymerization (N arm) show two distinctly different regimes of response. The colloidal Regime I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 78 publications
1
39
0
Order By: Relevance
“…Indeed, independent experimental rheology measurements of similar GNPs revealed that these cage rearrangements occur on macroscopic time scales (up to several days in some cases). 55 In our simulations, we have achieved the first stage of equilibration, that is, local relaxation of the grafted chains, but the entire system has not reached equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, independent experimental rheology measurements of similar GNPs revealed that these cage rearrangements occur on macroscopic time scales (up to several days in some cases). 55 In our simulations, we have achieved the first stage of equilibration, that is, local relaxation of the grafted chains, but the entire system has not reached equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…2,5 At extreme functionalities ( f ≈ 900), they are less soft than at f = 128 and can be considered as approaching the hard sphere limit. 26 In such a case, particle scale excluded volume effects dramatically slow down their center-of-mass motion resulting in caging, and the stars jam over the time scales corresponding to the experimental frequency window, like microgel particles, emulsions, or foams. 2,27,28 This unexpected behavior arises from the extremely high branching functionality and the short arm length.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…15 Moreover, recent data with polystyrene-grafted silica nanoparticle melts having constant grafting density and varying molar mass of polystyrene also comply with this picture. 26 Hence, the representation of Figure 4 should be generic. However, given that stars and grafted nanoparticles are different (particularly with respect to core size), we prefer to restrict our discussion to well-defined stars of the same chemistry, while pointing out the analogies with other systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft particle glasses (SPGs) are amorphous materials made of deformable particles which are packed at large volume fractions above the jamming transition [1,2]. Important examples include concentrated emulsions [1], microgel suspensions [3], and concentrated dispersions of hairy particles such as star polymers [4,5] or grafted nanoparticles [6]. In SPGs, each particle is constrained in a cage by elastic repulsive forces and cannot move over long distances unless a mechanical action exceeding the yield point is applied.…”
Section: Introductionmentioning
confidence: 99%